2018
DOI: 10.1002/gcc.22537
|View full text |Cite
|
Sign up to set email alerts
|

A prolonged response to platinum‐based therapy in a patient with metastatic urothelial carcinoma harboring a single rearranged and truncated NF2 gene

Abstract: Tumor genome sequencing has become an invaluable resource in determining targets for new therapies. In this report, we describe the case of a patient with metastatic urothelial carcinoma with sarcomatoid features. Sarcomatoid differentiation is a rare histologic subtype that confers a more aggressive course. The first-line treatment for patients with urothelial carcinoma is platinum-based chemotherapy. Next generation tumor sequencing performed using the FoundationOne assay revealed loss of one NF2 allele and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The expression of ligands such as PD-L1, PD-L2 and CD80 (also known as B7.1/ CD28LG) on the tumor cell surface allow them to bind receptors on T-cells within the tumor microenvironment, such as PD-1 and CTLA4, to downregulate the host immune response (2,13). FDA approved immune checkpoint inhibitors such as ipilimumab (anti-CTLA4), pembrolizumab and nivolumab (humanized and fully human anti-PD-1 monoclonal antibodies, respectively) counteract this immune evasion and have shown promising responses (2,13). Response rates as high as 50% and durable response to therapy in many cases, with concurrent or sequential therapy with ipilimumab and nivolumab, in one study, highlight the success of these agents (2, 13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of ligands such as PD-L1, PD-L2 and CD80 (also known as B7.1/ CD28LG) on the tumor cell surface allow them to bind receptors on T-cells within the tumor microenvironment, such as PD-1 and CTLA4, to downregulate the host immune response (2,13). FDA approved immune checkpoint inhibitors such as ipilimumab (anti-CTLA4), pembrolizumab and nivolumab (humanized and fully human anti-PD-1 monoclonal antibodies, respectively) counteract this immune evasion and have shown promising responses (2,13). Response rates as high as 50% and durable response to therapy in many cases, with concurrent or sequential therapy with ipilimumab and nivolumab, in one study, highlight the success of these agents (2, 13).…”
Section: Discussionmentioning
confidence: 99%
“…The primary biomarker used to predict response to immunotherapeutic agents is PD-L1 protein expression assessed by immunohistochemistry, while others include CD8 positive Tcell density and specific transcriptional signatures (2,13). Recently TMB, a surrogate metric for assessing tumor immunogenicity by determining the load of neo-epitopes, has emerged as a promising biomarker for predicting response to immunotherapy (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that both samples shared the most recent common ancestor (MRCA) encompassing 23 mutations and an exon1-exon13 truncation of the neurofibromin 2 ( NF2 ) gene, indicating their common origin ( Figure 3 ). Notably, a double deletion of TP53 and RB1 was identified at the initiation of neuroendocrine stages, while a truncation of NF2 resulted in sensitivity to platinum chemotherapy ( 9 ). A specific subclone harboring 37 mutated genes and an AR amplification was observed in the M-sample.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%